2009
DOI: 10.1007/s00277-009-0870-z
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathological analysis of 303 cases with malignant lymphoma classified according to the World Health Organization classification system in a single institute of Taiwan

Abstract: Several reports have shown a different distribution of malignant lymphoma (ML) in Asian and Western populations. The purpose of our survey was to elucidate whether there are substantial differences in the frequencies of subtypes of ML between different geographical areas. All entities diagnosed as ML between June 1995 and December 2007 were selected according to the 2008 World Health Organization (WHO) classification and searched for clinical outcomes. The cases were retrieved and reviewed by a panel of clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
37
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 33 publications
8
37
0
Order By: Relevance
“…DLCBL accounts for 45% of all B-cell neoplasms in our study, while it represents more than 60% of all B-cell neoplasms in China (Yang et al, 2011) and Taiwan (Chen et al, 2010). Mantle cell lymphoma (MCL) represents 8% of all B-cell neoplasms, which exceeds by far the percentage of MCL in Saudi Arabia (2%) (Akhtar et al, 2009), Korea (3%) (Yoon et al, 2010), Thailand (1%) (Sukpanichnant, 2004), USA (3%) (Wu et al, 2009) and France (4%) (Troussard et al, 2009) (Table 2).…”
Section: Resultsmentioning
confidence: 54%
“…DLCBL accounts for 45% of all B-cell neoplasms in our study, while it represents more than 60% of all B-cell neoplasms in China (Yang et al, 2011) and Taiwan (Chen et al, 2010). Mantle cell lymphoma (MCL) represents 8% of all B-cell neoplasms, which exceeds by far the percentage of MCL in Saudi Arabia (2%) (Akhtar et al, 2009), Korea (3%) (Yoon et al, 2010), Thailand (1%) (Sukpanichnant, 2004), USA (3%) (Wu et al, 2009) and France (4%) (Troussard et al, 2009) (Table 2).…”
Section: Resultsmentioning
confidence: 54%
“…Although these data effectively characterize the subtype spectrum of lymphomas [18][19][20][21][22][23][24][26][27][28][29][30][31][32][33][34][35], most studies have excluded the majority of plasma cell neoplasms and leukemias (circulating phase). Therefore, these results may not be comparable with population-based incidence data for the entire spectrum of WHO classifications [10,42,43].…”
Section: Introductionmentioning
confidence: 74%
“…A previous pioneer study from North India has shown the incidence to be 44% (106 of 241 cases of NHLs over a 3 year period) (Singh et al, 2003). However, the incidence of pENL has been shown to be very high in neighbouring Pakistan and Saudi Arabia (up to 50%) (Nagi et al, 2011), Kuwait (45%) (Temmim et al, 2004), Northern Iraq (48.3%) (Yaqo et al, 2011), Taiwan (47.2%) (Chen et al, 2010), Japan (46.6%) (Fujita et al, 2009), Korea (55%) (Yoon et al, 2010), Thailand (58.7%), and China (44.9%-61.4%) (Yang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…), skin, central nervous system (CNS), bone, testis, thyroid, breast, orbit, and rarely adrenal, pancreas, and the genitourinary tract (Singh et al, 2003;Temmim et al, 2004;Al Shemmari et al, 2008;Aoki et al, 2008;Gross et al, 2008;Lal et al, 2008;Fujita et al, 2009;Chen et al, 2010;Yoon et al, 2010;Yun et al, 2010;Arora et al, 2011;Nagi et al, 2011;Yaqo et al, 2011;Yang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%